Covalent bonding and hybridization effects in the corundum-type transition-metal oxides V2O3 and Ti2O3 - Eyert, V; Schwingenschloegl, U; Eckern, U (arXiv.org, 2005)
The electronic structure of the corundum-type transition-metal oxides V2O3 and Ti2O3 is studied by means of the augmented spherical wave method, based on density-functional theory and the local density approximation. Comparing the results for the vanadate and the titanate allows us to understand the peculiar shape of the metal 3d a_{1g} density of states, which is present in both compounds. The a_{1g} states are subject to pronounced bonding-antibonding splitting due to metal-metal overlap along the c-axis of the corundum structure. However, the corresponding partial density of states is strongly asymmetric with considerably more weight on the high energy branch. We argue that this asymmetry is due to an unexpected broadening of the bonding a_{1g} states, which is caused by hybridization with the e_g^{pi} bands. In contrast, the antibonding a_{1g} states display no such hybridization and form a sharp peak. Our results shed new light on the role of the a_{1g} orbitals for the metal-insulator transitions of V2O3. In particular, due to a_{1g} - e_g^{pi} hybridization, an interpretation in terms of molecular orbital singlet states on the metal-metal pairs along the c-axis is not an adequate description.